Задание: 1. Решить уравнение:
а) 6x - 3 = 4х + 1;
6) 2(4х + 2) = 3( 2х + 1) + 2х:
в) 5( 3х + 2) - 4х = 11х + 10.

Лтвет Лтвет    1   11.11.2020 09:04    1

Ответы
nexorosheva06 nexorosheva06  11.11.2020 09:10

ответ:1) 6x - 3 = 4x + 1

6x - 4x = 1 + 3

2x = 4

x = 2

2) 2(4x + 2) = 3(2x + 1) + 2x

8x + 4 = 6x + 3 +2x

8x + 4 = 8x + 3

8x - 8x = 3 - 4

0 * x = - 1- корней нет

x ∈ ∅

3) 5(3x + 2) - 4x = 11x + 10

15x + 10 - 4x = 11x + 10

11x -11x = 10 - 10

0 *x = 0

x ∈ R

4) 3x + 7 - (x + 8) = 5

3x + 7 - x - 8 = 5

2x - 1 = 5

2x= 6

x = 3

ответ : при x = 3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра